Low Nitrogen Fertilization Alter Rhizosphere Microorganism Community and Improve Sweetpotato Yield in a Nitrogen-Deficient Rocky Soil - Ding, Yanqiang; Jin, Yanling; He, Kaize; Yi, Zhuolin; Tan, Li; Liu, Lisha; Tang, Mingshuang; Du, Anping; Fang, Yang; Zhao, Hai (Frontiers in Microbiology, 2020)
Sweetpotato can be cultivated in reclaimed rocky soil in Sichuan Basin, China, which benefits from the release of mineral nutritions in rocky soil by microorganisms. Shortage of nitrogen (N) in rocky soil limits sweetpotato yield, which can be compensated through N fertilization. Whereas high N fertilization inhibit biological N fixation and induce unintended environmental consequences. However, the effect of low N fertilization on microorganism community and sweetpotato yield in N-deficient rocky soil is still unclear. We added a low level of 15 kg/ha urea to a rocky soil cultivated with sweetpotato, and measured rocky soil physiological and biochemical properties, rhizosphere microbial diversity, sweetpotato physiological properties and transcriptome. When cultivating sweetpotato in rocky soil, low N fertilization not only improved total N (TN) and available N (AN) in rocky soil, but also increased available phosphorus (AP), available potassium (AK), and nitrogenase and urease activity. Interestingly, although low N fertilization could reduce bacterial diversity through changes of sweetpotato root exudates and rocky soil properties, the relative abundance of P and K-solubilizing bacteria, N-fixing and urease-producing bacteria increased under low N fertilization, and relative abundance of plant pathogens decreased. Furthermore, low N fertilization increased the phytohormones, such as zeatin riboside (ZR), abscisic acid (ABA), and methyl jasmonate (MeJA) contents in sweetpotato root. Those increases were consistent with our transcriptomic findings: the inhibition of the lignin synthesis, the promotion of the starch synthesis, and the upregulated expression of Expansin, thus resulting in promoting the formation of tuberous roots and further increasing the sweetpotato yield by half, up to 33.3 t/ha. This study indicated that low N fertilization in the N-deficient rocky soil improved rocky soil quality through affecting microorganism community, and further increased sweetpotato yield under regulation of phytohormones pathway.